FAKTOR- FAKTOR PENYEBABKAN TERJADINYA PLAGIATISME PADA MAHASISWA FKIP UNIVERSITAS TANJUNGPURA - Dewantara, Jagad Aditya; Riyanti, Dwi; Yansa, Hemri; Chorina, Malisa (Universitas Tanjungpura, 2023)
AbstractAdvances in technology, especially the internet, have made it possible for all people to find information quickly. In line with this convenience, plagiarism is increasingly happening in the world of education, especially universities. This study focuses on four factors that cause plagiarism in students which were identified by reviewing using the relevant literature. Namely, academic culture factors, organizational factors, the role of supervisors, and individual factors. This study uses a qualitative research method with a case study design on FKIP students at Tanjungpura University with the research subject of lecturers. This study uses a semi-structured interview technique. From the results of qualitative data analysis, it was found that internet abuse, poor assessment practices, and lack of academic writing skills were some of the factors causing plagiarism by students. The implications of this study indicate the need for all universities in Indonesia to encourage lecturers to remind students of the serious consequences of academic dishonesty and point out some examples of plagiarism.